Gestión integral de residuos químicos generados en actividades industriales - Loayza-Pérez, Jorge (2009)
Integral management of chemical wastes generated in industrial activitiesThe integral management of chemical wastes allows to d iminish the amount of generated wastes, to reutilize wastes so as to diminish their danger, and to make safe use of the final disposition of those wastes that cannot be reduced. Here we present the principies of chemical wastes management, the analysis of the service I ife of a waste and diverse treatment options (physical, chemical, thermal and biological) for its final disposition